Design and Development of EcoSense: Android-Based Incentivized Environmental Campaign App - Deddy Romnan Rumapea; Kenrick Tandrian; Rivano Ardiyan Taufiq Kurniawan; Mirsa Salsabila; Darren Ngoh; Kenji Marwies; Bukhori Muhammad Aqid; Ade Azurat (Jurnal Ilmu Komputer dan Informasi, 2023)
This research paper presents the design and development of EcoSense, an Android-based incentivized environmental campaign app, using the Design Science Research Methodology (DSRM). The DSRM approach involved six steps: problem identification, objective definition, design and development, demonstration, and evaluation. The problem of insufficient participation in environmental activities in Indonesia was identified using the Five Whys method, and user requirements were collected through an online survey. Various design artifacts were created to ensure the app is user-friendly, and the app was evaluated based on user engagement and participation. The results suggested that the app has the potential to effectively engage users in environmental campaigns, as evidenced by the relatively high retention and conversion rates. The study has some limitations, such as a small sample size and limited evaluation metrics, but future research can address these limitations and expand on the findings.